2013
DOI: 10.1021/ol401709t
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of a Pyrroloindoloquinazoline Alkaloid

Abstract: A highly concise stereoselective synthesis of a newly identified alkaloid with a pyrroloindoloquinazoline skeleton has been achieved. To this end, a chiral auxiliary mediated asymmetric acetate aldol reaction on tryptanthrin was explored and the resulting adduct was converted to the product by a novel one-pot reductive cyclization/transamidation using NiCl2·6H2O/NaBH4 in methanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…These results clearly demonstrated that ionic liquids 1 and 2 are excellent microwave absorbers, and these ionic solvents outperformed the molecular solvent DMF in the one-pot synthesis of tryptanthrin. Moreover, under our experimental conditions, toluene, a commonly used solvent for the synthesis of tryptanthrin, produced no trace of tryptanthrin (entries 8 and 9, Table 1) [19,[22][23][24][25][26][27][28][29][30]. Although poor isolated yields of tryptanthrin were obtained in the ionic liquid 1 and DMF without the use of any base, ionic liquid 1 nevertheless produced a higher tryptanthrin yield than DMF: 19% versus 6%, respectively (entries 6 and 7, Table 1).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…These results clearly demonstrated that ionic liquids 1 and 2 are excellent microwave absorbers, and these ionic solvents outperformed the molecular solvent DMF in the one-pot synthesis of tryptanthrin. Moreover, under our experimental conditions, toluene, a commonly used solvent for the synthesis of tryptanthrin, produced no trace of tryptanthrin (entries 8 and 9, Table 1) [19,[22][23][24][25][26][27][28][29][30]. Although poor isolated yields of tryptanthrin were obtained in the ionic liquid 1 and DMF without the use of any base, ionic liquid 1 nevertheless produced a higher tryptanthrin yield than DMF: 19% versus 6%, respectively (entries 6 and 7, Table 1).…”
Section: Resultsmentioning
confidence: 91%
“…All these intriguing biological activities from tryptanthrin justify the study for its improved synthesis as a useful scaffold for drug discovery and the advanced development as anti-microbial, anti-inflammatory, and anti-neoplastic agents. Many syntheses of tryptanthrin were reportedly achieved under basic and refluxing conditions (e.g., Et3N in refluxing toluene for 16 h) [19,[22][23][24][25][26][27][28][29][30]. As one example, Srinivasan and co-workers reported the two steps synthesis of tryptanthrin in moderate (54%) isolated yield involving the use of LDA and starting from anthranilic acid, methyl anthranilate, and ethyl orthoformate [26].…”
Section: Resultsmentioning
confidence: 99%
“…45 Tryptanthrin (67) was transformed into (+)-(S,S)-cruciferane (25) via a chiral auxiliarymediated asymmetric aldol reaction followed by the one-pot reductive cyclization/transamidation of 70 with NiCl 2 /NaBH 4 (Scheme 16). 46 The selective insertion of in situ-generated aryne 72 to the 3-position nitrogen of 1,3-quinazoline was developed to prepare fused quinazolinone. Based on the one-pot protocol, phaithanthrins B (73) and C (74), 67, 69, and 25 were synthesized (Scheme 17).…”
Section: Non-tryptaminesmentioning
confidence: 99%
“…36 Tryptanthrin (101) was prepared from isatoic anhydride 92 using a known procedure. 36 Tryptanthrin (101) was prepared from isatoic anhydride 92 using a known procedure.…”
Section: Tryptanthrin and Phaitanthrin Alkaloidsmentioning
confidence: 99%